2022
DOI: 10.1039/d1ta08634k
|View full text |Cite
|
Sign up to set email alerts
|

Performance modulation through selective, homogenous surface doping of lanthanum strontium ferrite electrodes revealed by in situ PLD impedance measurements

Abstract: Accelerating the oxygen reduction kinetics of solid oxide fuel cell (SOFC) cathodes is crucial to improve their efficiency and thus to provide the basis for an economically feasible application of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
(159 reference statements)
0
6
0
Order By: Relevance
“…Indicated by the formation of a positive surface charge for basic decorations (negative for acidic decorations), we can further assume that basic decorations promote the formation of positively charged oxygen vacancies, which have been proposed to be a decisive factor for fast oxygen exchange kinetics. This hypothesis is also supported by the lower binding energy O 1s species measured on SrO-decorated PCO10 (and vice versa for SnO 2 -decorated PCO10, see Figure C). Nevertheless, independent of the exact nature of charge redistribution processes, it is evident that defect concentrations in the surface and subsurface will change upon decoration, altering oxygen exchange reaction rates, which contain contributions of both vacancy and electron concentrations.…”
Section: Mechanistic Discussionmentioning
confidence: 56%
“…Indicated by the formation of a positive surface charge for basic decorations (negative for acidic decorations), we can further assume that basic decorations promote the formation of positively charged oxygen vacancies, which have been proposed to be a decisive factor for fast oxygen exchange kinetics. This hypothesis is also supported by the lower binding energy O 1s species measured on SrO-decorated PCO10 (and vice versa for SnO 2 -decorated PCO10, see Figure C). Nevertheless, independent of the exact nature of charge redistribution processes, it is evident that defect concentrations in the surface and subsurface will change upon decoration, altering oxygen exchange reaction rates, which contain contributions of both vacancy and electron concentrations.…”
Section: Mechanistic Discussionmentioning
confidence: 56%
“…1. While for the perovskite based substrate LSGM (orthorombic, Imma), epitaxial growth of LSF is not surprising and was already shown in a previous study, 48 it is not obvious that LSF can grow epitaxially on GDC. However, studies in literature have already shown the epitaxial growth of the structurally similar LSC on a GDC buffer layer 42,49,50 with a 451 in-plane rotation.…”
Section: Structural Characterization and Surface Morphologymentioning
confidence: 71%
“…The PLD has been utilized to deposit porous perovskite electrodes, 157‐160 electrolytes layers such as CGO, 161,162 YSZ, 163 and SDC/LSGM bilayers 164 so far. The exact transfer of the composition of LSGM was not possible through PLD 165 .…”
Section: Fabrication Techniques For Sofcsmentioning
confidence: 99%